GRAMMATICAL ERRORS IN THESIS ABSTRACTS WRITTEN BY THE UNDERGRADUATE STUDENTS OF MANAGEMENT STUDY PROGRAM - Soraya Grabiella Dinamika (JOALL (Journal of Applied Linguistics and Literature), 2021)
This research aims at analyzing the grammatical errors in English abstracts of the undergraduate thesis. This research takes place at two private colleges in Medan city which provide the undergraduate program of management study namely Sekolah Tinggi Ilmu Manajemen Sukma Medan and Sekolah Tinggi Ilmu Ekonomi Eka Prasetya. There are 20 abstracts taken as the data which are gathered from those colleges. This research engages with a qualitative descriptive approach. The data were analyzed by using the Error Analysis Method by Gass and Selinker. Based on the analysis, the categories of the grammatical errors found are the subject-verb agreement in the use of tense agreement and number agreement, and the use of the article ‘a/an/the’. The research findings show that the tense agreement error is 80, the number agreement error is 10, the omission of article a/an is 4, the omission of article ‘the’ is 153, the addition of article ‘a/an’ is 1, and the addition of article ‘the’ is 8. Hence, there are 300 grammatical errors found. Meanwhile, there are two sources of the grammatical errors; they are inter-language error and intra-language error. Yet, four factors cause grammatical error namely indeterminacy, inconsistency, simplification, and overgeneralization. Based on the findings, the researcher gives constructive pedagogical remediation which is directed to the EFL learners, English language instructor, and the syllabus developer.